Energy consumption, greenhouse gas emissions and economic feasibility studies of biodiesel production from Mahua (Madhuca longifolia) in India - Tirkey J.V.; Kumar A.; Singh D.K. (My University, 2025)
The application of biodiesel plays a substantial role to mitigate fossil fuel consumption and greenhouse gas emissions. Moreover, the major public concerns are about the sustainability of alternate fuel, economic benefit in the production, and adverse environmental impact. Hence, an intensive study of agriculture-associated biodiesel production is required for sustainability. In this study, mass, energy, and market value-based data allocation methods have been adopted for the assessment of Mahua tree cultivation to biodiesel production in terms of energy, economic, and CO2 emission. The results show the positive value for sustainability in terms of net energy gain (168.68 GJ/ha), energy use efficiency (3.8), energy efficiency ratio (1.498), and specific energy (26.31 MJ/kg). The economic profitability starts from the 14th year of cultivation, where the net present value (NPV) and internal rate of return (IRR) are 402.02 USD and 12%, respectively. In the 20th year, the NPV and IRR were estimated to the value of 4,971.30 USD and 28%. The equivalent CO2 emission with conduct allocation was estimated as 624.31, 21.92, and 1,947.28 kg ha−1 on the plantation, 9th and 20th year of the tree, respectively. The total greenhouse gas (GHG) emission was assessed to be 17.291-ton CO2-eq/ha over the sum of 20 years. However, the average CO2 accumulation as credit is predicted to be 0.0167 kg-CO2 eq/MJ/ha/year. © 2022 Elsevier Ltd